The knowledge of Tarnobrzeg residents on diabetes type II and the educational needs - preliminary - Jadach, Aneta (Journal of Education, Health and Sport, 2018)
Admission. Type II diabetes is still a significant problem of civilization. Despite medical advances observed increase in the incidence of this disease entity, which adversely affects the health situation in Poland. The primary step in the fight against proliferation of type II diabetes is to increase the awareness of people about lifestyle, which may be included risk factors of the disease and thus increase in cases in the macro scale. Objective of the work. Assessment of the level of knowledge of the selected group of healthy adult residents of Tarnobrzeg about type II diabetes and risk factors for this disease. Materials and methods. The study was conducted in April 2018 under the district of Tarnobrzeg. In the study, 104 people took part. Among those surveyed, most were men. The method used in the study was a diagnostic survey and questionnaire technique author. Application of the basic statistical analysis using the Pearson chi-square. Conclusions.The level of knowledge respondents is insufficient to take action and protect behavior and reduce the risk of developing diabetes type 2. At the same time, however, the vast majority of both women and men believe that proper education can minimize the incidence of type II diabetes.